Enhancing LVRT Capability of DFIG-Based Wind Turbine Systems with SMES Series in the Rotor Side - Xiao Zhou; Yuejin Tang; Jing Shi (International Journal of Rotating Machinery)
The necessary Low Voltage Ride Through (LVRT) capability is very important to wind turbines. This paper presents a method to enhance LVRT capability of doubly fed induction generators- (DFIGs-) based wind turbine systems with series superconducting magnetic energy storage (SMES) in the rotor side. When grid fault occurs, series SMES in the rotor side is utilized to produce a desired output voltage and absorbs energy. Compared with other methods which enhance LVRT capability with Superconducting Fault-Current Limiter-Magnetic Energy Storage System (SFCL-MESS), this strategy can control the output voltage of SMES to suppress the transient AC voltage component in the rotor directly, which is more effective and rapid. Theoretical study of the DFIG under low voltage fault is developed; the simulation results are operated by MATLAB/Simulink.